Modeling-Enabled Systems Nutritional Immunology - Verma, Meghna; Hontecillas, Raquel; Abedi, Vida; Leber, Andrew; Tubau-Juni, Nuria; Philipson, Casandra; Carbo, Adria; Bassaganya-Riera, Josep (Frontiers in Nutrition, 2016)
This review highlights the fundamental role of nutrition in the maintenance of health, the immune response and disease prevention. Emerging global mechanistic insights in the field of nutritional immunology cannot be gained through reductionist methods alone or by analyzing a single nutrient at a time. We propose to investigate nutritional immunology as a massively interacting system of interconnected multistage and multiscale networks that encompass hidden mechanisms by which nutrition, microbiome, metabolism, genetic predisposition and the immune system interact to delineate health and disease. The review sets an unconventional path to applying complex science methodologies to nutritional immunology research, discovery and development through ‘use cases’ centered around the impact of nutrition on the gut microbiome and immune responses. Our systems nutritional immunology analyses, that include modeling and informatics methodologies in combination with pre-clinical and clinical studies, have the potential to discover emerging systems-wide properties at the interface of the immune system, nutrition, microbiome, and metabolism.